Series of Cases with Iatrogenic Nerve Injury - Daisy, Selina; Mohammad, Quazi Deen; Hoque, Azharul; Alam, Badrul; Haque, Badrul; Rahman, Kazi Mohibur; Khan, Sharif Uddin (Journal of Bangladesh College of Physicians and Surgeons, 2010)
After introduction of EMG at Dhaka Medical Collage on January 01, 2006, a total of 415 cases referred to EMG laboratory for electrophysiological evaluation over a period of two years (January 01, 2006 to December 31, 2007). Among these, 7 cases diagnosed as iatrogenic nerve injuries. The subtypes of iatrogenic nerve injuries were: 1. Accessory nerve injury: three, 2. Femoral nerve injury: one, 3. Sciatic nerve injury: one, 4. Lumbar sacral plexus injury: one, 5. Combined sciatic and femoral nerve injury: one In order to investigate the causes, diagnosis & prevention of iatrogenic nerve injuries; we have reviewed 7 cases of iatrogenic nerve injuries. The peripheral nerve injuries occurred due to lack of proper awareness of medical personals. These injuries are iatrogenic injuries so it is useful to review the mode of injuries and means of prevention. DOI: 10.3329/jbcps.v28i2.5373 J Bangladesh Coll Phys Surg 2010; 28: 121-124